Optimizing Interactive Reading Techniques to Improve Student Literacy at MI Al Hidayah - Firmansyah, Arif; Auliya, Silma Nur Rifa; Azzahra, Siti Lutfiah; Jamaludin, Agus Muhamad; Mansur, Muhammad Hilmi Futhoni; Ihsan, Muhamad; Marlina, Ine; Mulyani, Cici Sri; Permana, Fera Nursantika; Zahra, Nurul Aulia; Hidayat, Alsira Rifa (CV. Rayyan Dwi Bharata, 2025)
The research aims to increase students' literacy interest at MI Al Hidayah by implementing interactive reading techniques. By using a qualitative descriptive approach and direct observation, this research identifies factors that influence low interest in literacy. The research results show that interactive reading techniques are effective in increasing students' interest and literacy skills. Oral interactions, parental involvement, and innovative learning technologies also contribute to increased literacy. Research concludes that interactive reading techniques can improve students' literacy abilities by developing interaction-based reading skills, preparing them to face the digital era. Implications include increased collaboration between teachers, students, and parents, as well as the use of technology to strengthen program literacy.